(untitled) (Minerva, 2019)
The aim of this article is to show some of the difficulties that entailed the translation of a Greek scientific text made by Alfanus of Salerno and Burgundio of Pisa, from the original by Nemesius Emesenis, —the anthropological work Περὶ φύσεως ἀνθρώπου, also called De natura hominis, written ca. 400 A.D.— in Italy during the 11th and 12th centuries, when Greek language was still virtually unknown in the rest of the Western countries. There are two sections: A short introduction about Nemesius, his treatise and the two medieval translators. 2. A brief account about the main problems of this translation process.